Baseline evaluation of Akorion’s EzyAgric innovation platform - Ogutu, Sylvester; Kikulwe, Enoch; Ajambo, Susan; Birachi, Eliud (International Food Policy Research Institute, 2023)
Digital innovations, for instance, in extension, finance, and logistics can play an important role in agri-food systems. They can address bottlenecks in access to extension services, marketing systems, suitable financial products, reliable weather information, transport services and logistics as well as supply chain management. For the benefits of digital innovations to be realized, the innovations must be adopted at scale. The literature, however, shows that the reach of digital innovations is limited by challenges, such as lack of awareness of existing innovations and information asymmetries in different contexts. This was also evident from a recent scoping study that we conducted in Uganda. The scoping study was conducted under the CGIAR‘s initiative on Rethinking Food Markets and Value Chains for Inclusion and Sustainability. The initiative aims to transform value chains through policies that ensure creation of efficient, inclusive value chains with equitable income sharing, greater job creation and adoption of sustain able practices among small and medium enterprises and smallholder farmers, especially women and youth. The scoping study revealed that access to digital innovations is hampered by low awareness of existing innovations, limited digital literacy, and social norms and power relations in some segments of the population, such as the women and youth. Against this background, we designed an intervention including digital literacy training and awareness creation that we intend to implement through a randomized controlled trial (RCT) to address the information gap in the literature. The RCT will entail a treatment group which will receive digital literacy training coupled with some basic agronomic training. The control group will not receive training. To help us implement the intervention, we partnered with Akorion Limited (EzyAgric), a digital innovations company that promotes the use of bundled digital technologies in the agrifood sector in Uganda. The bundled services include farm management services, linking farmers with agro-input providers, credit access, extension services, and linking farmers to product markets. As a starting point to the planned intervention, we designed and implemented a base line study. The baseline survey covered 536 households in five districts of central Uganda, with 282 households randomly assigned into the treatment group, and 254 households randomly assigned into the control group. Preliminary results from the baseline survey revealed that the means or averages of main indicators, such as inorganic fertilizer use, credit access, and wel fare measures (e.g., revenue from crop harvest and non-farm business operations) do not differ significantly between famers in the treatment and control groups. Livestock revenues, con sumption expenditure, household food insecurity experience scale and the value of assets were also found to be statistically insignificant between the two groups. This suggests that the ran domization worked and provides a basis for simple comparison of mean outcomes in the follow up survey. However, for some variables, such as the use of fungicides and total value of pro duction, the differences between the treatment and control group were statistically significant. In such cases where the variables are unbalanced, analysis of covariance (ANCOVA) or regression analysis with the control variables, such as the difference-in-differences regression will be estimated to net out the effects of the intervention.